Misinterpretation of the Hadith of Luzūm Al-Jamā'ah and Its Impact on Social Interaction within the LDII Community in Samarinda City - Abdul Majid (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This article aims to describe LDII's understanding of the hadith about being consistent with the congregation, analyze their understanding concerning the understanding of scholars, and describe the impact of this understanding on their social interactions with the general public. The research method is quantitative with a phenomenological analytical descriptive approach. They obtained the data through interviews with four categories.: LDII administrators/mullahs, former LDII members, "chameleons" (LDII members who started to doubt LDII teachings), and the general public. As a result, they understand that the congregation referred to in the hadith is the LDII congregation because it is the only one with an imam consistent with the Qur'an and the hadith is alleged and obeyed correctly. The Imam in question is Nur Hasan al-Ubaidah and his successors. It has an impact on their social interaction behaviour towards non-LDII communities, such as refusing to pray other than in LDII mosques, refusing to mimic non-LDII Imams, refusing to attend non-LDII recitations, refusing to marry non-LDII, requiring divorce from non-LDII husbands and wives, "nikah dalam" marriages within LDII, termination of inheritance rights for non-LDII, separation of pilgrims from government groups. Such understanding aims to build solidity and fanaticism towards LDII and protect them from the influence of non-LDII teachings. In conclusion, this interpretation is deviant because it bases itself on something other than the rules set by scholars. Their subjectivity appears to lead the hadith to the desired meaning and leads to truth claims and takfiri